Intervensi Keperawatan dalam Pencegahan Depresi Postpartum pada Ibu Nifas - Siti Khotimah; Faizah Bety Rahayuningsih (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to identify the role of nursing interventions in preventing postpartum depression in postpartum mothers. The method used was a systematic review following the PRISMA 2020 guidelines using the PubMed, CINAHL, Scopus, and Science Direct databases for articles published between 2013 and 2024. The results showed that of the 1,248 articles identified, 12 studies met the inclusion criteria. The nursing interventions identified included mental health education, postpartum depression screening, nursing counseling, home visits, and psychosocial support. Most studies demonstrated a significant reduction in postpartum depression scores and improvements in maternal psychological well-being, such as decreased anxiety and increased self-confidence. In conclusion, postpartum nursing interventions play a crucial role in preventing postpartum depression and are recommended for integration into routine postpartum care. Keywords: Postpartum Depression, EPDS, Postpartum Mothers, Nursing Interventions